Characteristics and Epidemiology of Extended-Spectrum β-Lactamase-Producing Multidrug-Resistant Klebsiella pneumoniae From Red Kangaroo, China - Wang, Xue; Kang, Qian; Zhao, Jianan; Liu, Zhihui; Ji, Fang; Li, Junbao; Yang, Jianchun; Zhang, Chenglin; Jia, Ting; Dong, Guoying; Liu, Shelan; Hu, Guocheng; et al. (Frontiers in Microbiology, 2020)
Due to its drug resistant nature, β-lactamase represents a serious challenge for public health. Extended-spectrum β-lactamase (ESBL) producing Klebsiella pneumoniae clones are increasingly reported worldwide. Little is known about the prevalence and biological characteristics of drug-resistant strains in zoos. During routine surveillance at the Zhengzhou Zoo of China, we found Klebsiella pneumoniae isolate in healthy Red Kangaroos (Macropus Rufus) with severe MDR. The Klebsiella pneumoniae were especially resistant to Cefuroxime Sodium (MIC, > 64 μg/mL), Ceftriaxone (MIC, >8 μg/mL) and Cefepime (MIC, >64 μg/mL), and belonged to ST290. Subsequently, whole genome sequencing (WGS) showed that the Chrome Chr-M297-1 harbored blaDHA–3, blaSHV–1, blaCTX–M–14, fosA5, dfrA3, sul3, etc., and pM297-1.1 [222,864 bp, IncFIB(K)], which carried nine antimicrobial genes including blaCTX–M–14, blaTEM–191, aph(3″)-Ib, aph(6)-Id and qnrS1, etc., and pM297-1.2 [225,763 bp, IncFII(K)] carried 22 antimicrobial genes including blaTEM–1, blaCTX–M–3, aph(3′)-Ia, aac(3)-IIa, aac(6′)-Ib-cr, aadA16, qnrB2, qnrS1, qacEΔ1, mphA, sul1, and dfrA27, etc. A traceability analysis then revealed that these two plasmids were highly similar to those recovered from human clinical samples in some southern cities in Sichuan Province, China (>99%), suggesting that these plasmids are spreading in China. Furthermore, two plasmids harboring conjugal transfer genes facilitated the transmission of antimicrobial genes by conjugation with E. coli J53. Our research shows that the transmission and adaptation of Klebsiella pneumoniae producing ESBLs is occurring in zoo environments, suggesting that zoos may be becoming important potential reservoirs for clinically important drug-resistant genes. It is therefore necessary to monitor the emergence and spread of drug-resistant gene strains in captive wild animals held in zoo environments.